1989
DOI: 10.1115/1.3265699
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stability of Liquid-Filled Cylindrical Shells Under Periodic Shearing Forces

Abstract: Theoretical analyses are presented for the dynamic stability of a cylindrical shell partially filled with liquid, under periodic shearing forces. In the analyses, the dynamic version of the Donnell equations and the velocity potential theory are used for the motions of the shell and the contained liquid, respectively. The problem was solved by using the Galerkin method and the equations of motions coupling the shell and the liquid were derived from a type of coupled Mathieu’s equation. The instability boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Shibata [1] [2] had investigated the failures of cylindrical liquid storage due to seismic excitation and summarized the failures of the liquid storage tanks. As for the analytical procedures, Combescure et al [3] ,Liu and Uras [4] and Ito et al [5] reported dynamic buckling analysis, and Chiba et al [6] , Natsiavas and Babcock [7] , Hara et al [8] , and Shih et al [9] reported the instability phenomena found at the upper portion of the liquid storage tanks. Matuura, Kawamoto et al [10] conducted both experiments and analysis systematically on the buckling of thick walled cylindrical tanks with liquid sodium inside.…”
Section: Introductionmentioning
confidence: 99%
“…Shibata [1] [2] had investigated the failures of cylindrical liquid storage due to seismic excitation and summarized the failures of the liquid storage tanks. As for the analytical procedures, Combescure et al [3] ,Liu and Uras [4] and Ito et al [5] reported dynamic buckling analysis, and Chiba et al [6] , Natsiavas and Babcock [7] , Hara et al [8] , and Shih et al [9] reported the instability phenomena found at the upper portion of the liquid storage tanks. Matuura, Kawamoto et al [10] conducted both experiments and analysis systematically on the buckling of thick walled cylindrical tanks with liquid sodium inside.…”
Section: Introductionmentioning
confidence: 99%